Maturity Levels for E-commerce Adoption among Australian Retailers - Ibrahim, Waleed; Stevens, Kenneth (ACIS, 2014)
This study investigates the maturity levels of E-commerce (EC) among Australian retailers. It does this by developing a model that incorporates the possible stages of EC adoption by retailers and the factors that influence the adoption of each stage using combination of the SOG model and the TOE framework. The findings show that some retailers reach a stagnation point in their EC adoption and are unlikely to proceed further. In addition, the analysis suggests that the defined stages are influenced by environmental and organizational factors. However, these factors were found to have a different effect on each stage. The proposed model will be a useful tool for retail organisations to understand the current state of EC initiatives and to help them develop their EC business strategies.